Polymyxin Resistance Among XDR ST1 Carbapenem-Resistant Acinetobacter baumannii Clone Expanding in a Teaching Hospital - Carrasco, Letícia Dias de Melo; Dabul, Andrei Nicoli Gebieluca; Boralli, Camila Maria dos Santos; Righetto, Gabriela Marinho; Carvalho, Iago Silva e; Dornelas, Janaína Valerini; Martins da Mata, Camila Pacheco Silveira; Araújo, César Augusto de; Leite, Edna Mariléa Meireles; Lincopan, Nilton; Camargo, Ilana Lopes Baratella da Cunha (Frontiers in Microbiology, 2021)
Acinetobacter baumannii is an opportunistic pathogen primarily associated with multidrug-resistant nosocomial infections, for which polymyxins are the last-resort antibiotics. This study investigated carbapenem-resistant A. baumannii strains exhibiting an extensively drug-resistant (XDR) phenotype, including four isolates considered locally pan drug-resistant (LPDR), isolated from inpatients during an outbreak at a teaching hospital in Brazil. ApaI DNA macrorestriction followed by PFGE clustered the strains in three pulsotypes, named A to C, among carbapenem-resistant A. baumannii strains. Pulsotypes A and B clustered six polymyxin-resistant A. baumannii strains. MLST analysis of representative strains of pulsotypes A, B, and C showed that they belong, respectively, to sequence types ST1 (clonal complex, CC1), ST79 (CC79), and ST903. Genomic analysis of international clones ST1 and ST79 representative strains predicted a wide resistome for β-lactams, aminoglycosides, fluoroquinolones, and trimethoprim-sulfamethoxazole, with blaOXA–23 and blaOXA–72 genes encoding carbapenem resistance. Amino acid substitutions in PmrB (Thr232Ile or Pro170Leu) and PmrC (Arg125His) were responsible for polymyxin resistance. Although colistin MICs were all high (MIC ≥ 128 mg/L), polymyxin B MICs varied; strains with Pro170Leu substitution in PmrB had MICs > 128 mg/L, while those with Thr232Ile had lower MICs (16–64 mg/L), irrespective of the clone. Although the first identified polymyxin-resistant A. baumannii strain belonged to ST79, the ST1 strains were endemic and caused the outbreak most likely due to polymyxin B use. The genome comparison of two ST1 strains from the same patient, but one susceptible and the other resistant to polymyxin, revealed mutations in 28 ORFs in addition to pmrBC. The ORF codifying an acyl-CoA dehydrogenase has gained attention due to its fatty acid breakdown and membrane fluidity involvement. However, the role of these mutations in the polymyxin resistance mechanism remains unknown. To prevent the dissemination of XDR bacteria, the hospital infection control committee implemented the patient bathing practice with a 2% chlorhexidine solution, a higher concentration than all A. baumannii chlorhexidine MICs. In conclusion, we showed the emergence of polymyxin resistance due to mutations in the chromosome of the carbapenem-resistant A. baumannii ST1, a high-risk global clone spreading in this hospital.